FENOFISIOLOGI PERKECAMBAHAN DAN PERTUMBUHAN BIBIT DUKU(The Phenophysiology Of Germination and Growth Of Duku Seedling (Lansium Domesticum Corr.)) - . Irianto (Bioplantae, 2012)
This research was conducted to evaluate the Duku germination and its growth.Research used descriptive analysis to examine Duku’s germination. To makeduku germinated it used six tubs that used sand as media. After fourth weekgermination, the seedling was transplanting into polybags. The polybags mediaused soil with organic manure. The parameters that observed are percentage ofgermination, percentage of normal and abnormal seedling, percentage ofpolyembrioni seedling, root and shoot growth. The result showed that theamount of normal seedling 80 %, abnormal seedling 20 %, and polyembrioni 25%. Duku seedling grows normally until six weeks after germination are 40 %and Duku Seedling with uniform growth after six months about 20 %.Key words : Seed, poliembriony, vigor.